The Mediating Role of Sense of Meaning in Life and Negative Cognitive Emotions: An Assessment of the Impact of Stressful Events on the Mental Health of Cancer Patients During the COVID-19 Pandemic - Li, Yanghua; Zhang, Shun; Ali, Anwar; Babar, Quratulain; Tabassum, Huma (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: The COVID-19 pandemic posed significant challenges for cancer patients, intensifying psychological stress and compromising mental health. This study examined the relationships between stressful life events, sense of meaning in life, negative cognitive emotions, and mental health outcomes. Materials and Methods: A mediation analysis was conducted to explore both direct and indirect pathways, with cognitive emotions and sense of meaning of life acting as mediators. Data collected from 250 cancer patients revealed significant correlations among the variables. Results: Stressful events were negatively associated with a sense of meaning in life (r=-0.1131, p<0.05) and positively associated with Negative cognitive emotions (r=0.1597, p<0.01). According to mediation analysis, the association between stressful events and mental health was partially mediated by negative cognitive emotions and a sense of meaning of life. The combined mediation pathway involving both factors accounted for a significant portion of the total effect. Path analysis confirmed strong predictive relationships, with stressful events and mediators explaining 98.9% of the variance in mental health outcomes (R²=0.989, F (5, 120)=7.569.91, p<0.001). A strong sense of meaning buffered effect of stress and promoted resilience in cancer patients. Conclusion: These findings highlight the mechanisms through which stressful events impact mental health in cancer patients during crises. They underscore the importance of interventions focused on cognitive-emotional regulation and fostering a sense of meaning to improve psychological outcomes. This research provides a foundation for developing tailored therapeutic strategies to support vulnerable populations during global crises like pandemics.
Keywords: COVID-19 Pandemic; Cancer Patients; Psychological Stress; Cognitive Emotions; Sense of Meaning